Upaya Meningkatkan Motivasi Narapidana Mengikuti Pembinaan Pondok Pesantren Di Lembaga Pemasyarakatan - Anggraini, Septiana Dwi (Syntax Literate, 2020)
Motivation as an effort to arouse or encourage inmates to do something in order to achieve their goals. One form of the motive for the crime is done again, namely the lack of motivation in prisoners to repent. In this case the Penitentiary has the duty and responsibility in the successful implementation of guidance for inmates who have a variety of cases. The boarding school guidance program provided to inmates must be implemented, but prisoners who sit in the middle to back row do not pay attention to the explanation given by the speaker. Because he considered the boarding school program aims to fulfill the obligation only. From this problem, it is necessary to carry out activities to motivate prisoners to participate in the program voluntarily and seriously. This is done in order to be able to provide good skills and mindset for Prisoners so that they have attitudes and principles of life that are filled with goodness. As well as changing and shaping convicts for the better and returning to the right path and do not have the thought of returning to commit crimes. This research was conducted with qualitative research methods by distributing questionnaires to determine the results of increased motivation in prisoners. It can be concluded that increasing motivation in inmates following the boarding school program requires innovation and new ways.